Philosophy as a Way of Life : Ancients and Moderns. - Chase, Michael (Wiley, 2013)
This unique collection of essays on the late Pierre Hadot's revolutionary approach to studying and practising philosophy traces the links between his work and that of thinkers from Wittgenstein to the French postmodernists. It shows how his secular spiritual exercises expand our horizons, enabling us to be in a fuller, more authentic way.Comprehensive treatment of a neglected theme: philosophy's practical relevance in our livesInterdisciplinary analysis reflects the wide influence of Hadot's thoughtExplores the links between Hadot's ideas and those of a we.